Situs Peninggalan Kerajaan Buton Sebagai Parawisata Kota Baubau - Ferdiansyah; Rismal Saktiawan (LANCAH: Jurnal Inovasi dan Tren, 2024)
This study attempts to know about management analysis tourism is in town baubau and how much impact contributions given by the tourism sector for the community and in terms of increasing local revenue for regional autonomy in the city Baubau. Conservation is based on three things namely the protection, maintenance and development of cultural heritage sites. People and tourists realize that many potential sites of the Sultanate of Buton must be preserved to support the development of heritage tourism Bau Bau City Southeast Sulawesi, Qualitative research methods with techniques for collecting data on data collection.